Part II. Drama / Choreography4. Physical Exercise in Highlighting The Professional Artistic Activities - Leşe Ana-Cristina (Sciendo, 2017)
The importance and utility of physical exercise in the life style of the artists has inspired us to write this paper through which we address the people from this field who want to start their own business. We launch this idea in order to provide employees a space for sports activities inside the company. A program of varied physical activity introduced as a break in the work program is an important element in the improvement of the human and professional resources. In this paper we describe: types of spaces equipped for physical exercises, work programs and several reasons that sustain the idea that a recreation back is very useful in the utility artistic professions of the modern world.